MAKNA AHL AL-KITĀB DALAM KONTEKS HUKUM PERKAWINAN MUSLIM DAN AHL AL-KITĀB - Sam'ani Sya'roni (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2013)
This article intends to (re) discuss about the position of ahl al-kitāb woman in the legal context of her marriage with a Muslim. Although thematically, this study has been carried out by experts, an interpretation approach used in this paper is expected to be as distinctive and produce a unique thought. According to khiṭāb Qur'an, that are called ahl al-kitāb are Jews and Christians. But some scholars expand the meaning scope of the ahl al-kitāb for all faiths whose holy book allegedly from God. Islam does not forbid people to marry with ahl al-kitāb. In other side, who is categorized scribes today is the problem. The controversial would be the root of the difference opinions among scholars that there are scholars who allow and forbid anyone on the basis of beneficiaries contains. However, the ability to marry the ahl al-kitāb is not a recommendation, so the positive and negative impacts should be considered in depth by Muslims.